Clinical and Radiological Indicators for Early Surgical Management in Pediatric Orbital Floor Fractures - Afsar, Hina; Siddiqui, Laraib; Yousaf, Adil; Moeedurehman, .; Hussain, Khaliq (Biological and Clinical Sciences Research Journal, 2025)
Early diagnosis and management of orbital floor fractures is of utmost importance, especially in the presence of periorbita incarceration. This study aims to assess the common indicators of orbital floor fracture in pediatric patients, both clinically and radiologically, so as to determine early surgical intervention in these patients. Methods: A retrospective cross-sectional study was carried out at the Oral and Maxillofacial ward of Lady Reading Hospital, Peshawar, from January 2021 to June 2024. Pediatric patients with an age range of 5-16 years of both genders, a history of trauma not more than 14 days, diplopia in primary and downward gaze, along with gaze restriction in any direction, enophthalmos, and confirmed orbital floor fracture in coronal view of CT scan were included in the study. The Ethical Review Board of Lady Reading Hospital approved the study protocol. A structured questionnaire was used to collect the data. The collected data was analysed using the Statistical Package for Social Sciences (SPSS) version 25. Results: The most common mechanism of injury recorded was RTA, with 65.7%. The children injured by fall were 22.5 %, 3.9% by assault, and 5.0% firearm injury. Among the clinical features recorded in the study, 40.2% had nausea/vomiting, 81.4% diplopia, and 57.8% had both exophthalmos and restricted eye movement. Among them, 82.4% had a confirmed orbital floor fracture on radiograph, while only 33.3% had the classical trapdoor sign evident on coronal CT. Conclusion: In conclusion of the study performed at our Centre, clinical findings should prompt a CT investigation in case of orbital fractures. If there is restriction of eye movement and diplopia along with other features, surgical intervention is necessary. Rest can be managed by conservative treatment.